56 Whole Exome Sequencing Identifies a Rare Mutation in NACAD as a Possible Cause of COVID orchitis in Brothers. Issue 1 (1st April 2022) - Reddy, R; Chertman, W; Efimenko, I; Kresch, E; Khodamoradi, K; Ramasamy, R
ABSTRACT: Introduction: Little is known of SARS-CoV2 (COVID-19) pathogenicity, but organ inflammation syndromes have been well observed and documented in the lungs, heart, liver, kidneys, and testes. While the blood-testis barrier is known to protect testes from antigens, current evidence suggests COVID-19 can affect the testis. Reports of bilateral orchitis are growing. Current hypotheses consider causes of (1) cellular induced cytokine storm or (2) IgG deposits in the vascular endothelium to be at blame but causal genes or underlying genetic susceptibility have not yet been identified. Objective: This project sought to uncover genetic explanations as to why certain men face increased susceptibility to developing COVID orchitis. Methods: We identified and examined six COVID-19 patients who all were confirmed with polymerase chain reaction (PCR), including three COVID-19 (+) men without orchitis (controls) and three COVID (+) men with orchitis (bilateral testicular pain for at least 5 days around the time of testing PCR positive). Of note, among the three men with COVID-19 who had orchitis, two of them were siblings. DNA extraction and whole exome sequencing were performed on blood using the QIAmp blood maxi kit on five of the six patients. Variants were prioritized by being shared between the three patients affected with orchitis, absent in controls, and introducing nonsense, frameshift, splicing or non‐synonymous amino acid changes and less than 10% in population prevalence. Based on WES findings, DuoSet® Human ACE2 reagent kit 2 (catalog number: DY933-05) was purchased from R&D Systems, USA, and used to measure the level of soluble ACE2 in the plasma samples. Results: The average age of the men in the study was 25 years old. The average duration of COVID symptoms (fever, sore throat, cough, body aches) were 7 days. Among the men who developed bilateral testis pain, the symptoms lasted for an average of 22 days. A list of 16 variants was generated that found to be shared between the two siblings with COVID orchitis along with the unrelated subject with COVID orchitis, and not present in the two controls. Among the 16 variants, a nonsynonymous non-frameshit deletion in NACAD variant on chromosome 7 with a frequency of 3.9% prevalence in ExAC was prioritized based on known involvement in the ACE2 pathway, read depth, and genotype quality. Phenotypically, we found that circulating levels of soluble ACE2 was 3.72 ng/ml among men who had COVID orchitis and was lower than men who developed COVID without orchitis. Conclusions: We observed a stop mutation in NACAD in 2 brothers and 1 unrelated man who developed COVID orchitis. Interestingly, we found lower circulating ACE2 serum levels in both brothers with orchitis and the one nonrelated orchitis subject but normal serum levels in all controls. NACAD when involved with cellular ability to shuttle out ACE2 becomes critical for COVID symptomatology. With decreased transcellular and extracellular transport of ACE2 being possible in subjects with the gene mutation, it can be postulated more ACE2 will be found intracellularly leading to increased cellular entry of SARS CoV-2 and possibility of orchitis sequelae. Disclosure: No